Nur77 ameliorates cyclophosphamide-induced ovarian insufficiency in mice by inhibiting oxidative damage and cell senescence - Ying Yao; Bin Wang; Kaihua Yu; Ji Song; Liyan Wang; Xia Yang; Xuehong Zhang; Yulan Li; Xiaoling Ma (BMC, 2024)
Abstract Premature ovarian failure (POF) is among the primary causes of ovarian dysfunction that severely affects women's physical and mental health. The main purpose of this study was to explore the expression level of Nerve growth factor-induced protein B (Nur77/NR4A1) in cyclophosphamide (CTX)-induced POF. We then tested whether Nur77 can exert a protective effect after CTX treatment and investigated the mechanism of Nur77's role during ovarian injury. CTX promotes follicular atresia by inducing redox imbalance, apoptosis, and senescence, thereby causing direct toxicity to gonads. Additionally, CTX decreases ovarian reserve consumption by stimulating the excessive activation of primordial follicles. Nur77 can be stimulated by oxidative stress, DNA damage, metabolism, inflammation, etc. However, its relationship with POF remains unelucidated. We here found that Nur77 is expressed at low levels in POF ovaries. Therefore, Nur77 was identified as a regulator of ovarian injury and follicular development. According to the results, Nur77 overexpression alleviated redox imbalances, reduced cell senescence and apoptosis, and improved follicular reserve. Nur77 protects ovarian function by restoring disordered sex hormone levels and estrus cycles and promoting follicle growth and development at all levels. Moreover, the rapamycin protein kinase (AKT)/mammalian target of the rapamycin (mTOR) is a crucial regulator of the primordial follicle pool and follicular development. A relationship was observed between Nur77 and AKT through string and molecular docking. Experiments confirmed the involvement of the AKT/mTOR signaling pathway in the regulatory role of Nur77 in ovarian function. Thus, Nur77 is a critical target for POF prevention and treatment.